External RF-EMF alters cell number and ROS balance possibly via the regulation of NADPH metabolism and apoptosis - Chow, Sheung-Ching; Zhang, Yang; Ng, Raymond W. M.; Hui, Shu-Yuen Ron; Solov’yov, Ilia A.; Lui, Wing-Yee (Frontiers in Public Health, 2024)
The influence of weak radio-frequency electromagnetic field (RF-EMF) on living organism raises new concern because of the ISM frequency band at 6.78 MHz being promoted by the AirFuel Alliance for mid-range wireless power transfer (WPT) applications and product development. Human exposure to the RF-EMF radiation is unavoidable. In this study, we employed in vitro cell culture and molecular biology approach coupled with integrated transcriptomic and proteomic analyses to uncover the effects of RF-EMF on cells at molecular and cellular levels. Our study has demonstrated that weak RF-EMF is sufficient to exert non-thermal effects on human umbilical vein endothelial cells (HUVEC). Exposure of weak RF-EMF promotes cell proliferation, inhibits apoptosis and deregulates ROS balance. Alteration of several signaling pathways and key enzymes involved in NADPH metabolism, cell proliferation and ferroptosis were identified. Our current study provide solid evidence for the first time that the present safety standards that solely considered the thermal effect of RF-EMF on cell tissue are inadequate, prompt response and modification of existing Guidelines, Standards and Regulation are warranted.